PEMETAAAN BIBLIOMETRIK TERHADAP PERKEMBANGAN PENELITIAN KOMUNIKASI ANTAR BUDAYA - Yunus Winoto; Rully Khairul Anwar; Syahla Nurlaeli Rahmi (JURNAL SIGNAL, 2024)
Intercultural communication is becoming an increasingly important topic in the development of globalization today. Judging from the rapid growth of direct contact between various countries and cultures, the exchange of information between individuals or groups from different cultural backgrounds is increasing. Intercultural communication is not only limited to the personal level, but also involves international organizations, businesses, and institutions. Increasing intercultural interaction in various aspects of life ultimately raises the need to understand the dynamics of intercultural communication more deeply, namely by conducting trend research through a bibliometric approach. This research can produce mature proposals regarding the dynamics of intercultural communication to date. According to Will Baker's bibliometric study from the University of Southampton, Southampton, the UK has high scientific results with 7 scientific papers that Will Baker has written having been cited 299 times, with an average of 42.71 citations per literary work. In terms of publications, the top published article discussing intercultural communication is the Journal Language and Intercultural Communication with 107 articles published and 1105 times cited. The phrase "intercultural communication" is the most relevant in its title, appearing 1110 times. The most common words in titles according to word clouds are "communication", "intercultural", "student", and "language" with 871, 626, 283, and 247 occurrences, respectively. The most common research focus in this field is intercultural communication, competence, language, culture, education, development and identity.